Observation of a quantum phase transition in the quantum Rabi model with a single trapped ion - M.-L. Cai (Nature Portfolio, 2021)
Quantum phase transition occurs in many-body systems with abrupt changes in the ground state around zero temperature. Here the authors report signatures of quantum phase transition in single trapped ion that can be described using quantum Rabi model.